Finance Cost and Revenue Retention in Nigeria - Obiora Peters; Amani Manzi Alain (International Journal of Global Sustainable Research, 2024)
This study's examination of the impact of public debt servicing on financing costs in Nigeria from 2000 to 2022 is necessary due to the growing conversation on the burdensome nature of public debt servicing. Using a population of bilateral and multilateral loan units and the universal sampling method, the study used an ex post facto research methodology. The dependent variable was revenue retention, while the variables of emphasis were loan servicing, loans from the World Bank, the IMF, and Paris Club. Diagnostics such as regression analysis, normality test, variance inflation factor, correlation matrix, and descriptive statistics analysis were used in the investigation. The findings showed that the Paris Club loan estimate had a positive but statistically insignificant impact, the World Bank and IMF loans had a statistically significant positive impact, and the loan servicing had a statistically significant negative impact on the public. It is recommended that World Bank funds should be employed to sectors that enhance revenue, such as improving tax administration, digitizing tax records, and expanding the tax base. Again, IMF loan should be more of strengthening fiscal operations. Prudent Borrowing is strictly advocated to reduce the heavy burden of debt which Nigeria current faces.